CCR: Cost‐aware cell relocation in 6TiSCH networks. Issue 1 (25th July 2017) - Chang, Tengfei; Watteyne, Thomas; Vilajosana, Xavier; Wang, Qin
Abstract: The Internet Engineering Task Force 6TiSCH Working Group standardizes the protocol stack for the Industrial Internet of Things, which combines the industrial performance of IEEE802.15.4 time‐slotted channel hopping (TSCH) with the addressability and Internet integration capabilities of Internet Protocol version 6. The 6top Protocol, which is part of 6TiSCH, allows distributed management of the TSCH communication schedule. The Scheduling Function Zero (SF0) is the default algorithm for a node to decide when to add/remove cells to its neighbors. SF0 picks the cells to add randomly; hence, it is possible that 2 nearby pairs of nodes pick the same cell, resulting in a schedule collision. This article introduces cost‐aware cell relocation (CCR), which is a solution to detect and fix such schedule collisions in a distributed manner. CCR monitors the performance of individual cells and uses that information to detect collisions. When such a collision is detected on a cell, neighbor nodes communicate to relocate that cell to a different slot/channel in the TSCH schedule. We implement CCR and run it on a 5‐node network on the Internet of Things Laboratory testbed. The results show that, compared with today's SF0 and for the same traffic requirements, CCR increases the average packet delivery ratio by 2% and reduces the number of cells that need to be scheduled by 27.3%. Abstract : We define "cell equivalence" and verify it on a large data set gathered in 8 experimental measurement campaigns. We design CCR and model its behavior mathematically and implement it practically on IoT‐Lab testbed. CCR is pushed through the standardization process at IETF 6TiSCH, with the goal for it to be accepted as the relocation algorithm of SF0.